A direct catalytic ring expansion approach to o-fluoronaphthols and o/p-fluorophenols from indanones and 2-cyclopentenones. Issue 84 (14th September 2015) - Chang, Jian; Song, Xiaoning; Huang, Wanqiao; Zhu, Dongsheng; Wang, Mang
Abstract : A catalytic ring expansion of indanones to o -fluoronaphthols is described by taking advantage of the multi-reactivities of TMSCF2 Br. Abstract : A direct method for the synthesis of o -fluoronaphthols and o / p -fluorophenols has been developed by a catalytic ring expansion of indanones and 2-cyclopentenones, in which TMSCF2 Br was used as a unique :CF2 source, a TMS transfer agent, as well as the Br − and F − releaser for the enolization, difluorocyclopropanation, desilylation, ring opening, defluorination, and aromatization sequence.